Pengaruh E-Lifestyle dan Budaya Digital Terhadap Perilaku Konsumtif Pemuda di Kota Malang - Ratna Puspita, Wyls; Muchsin, Slamet; Sunariyanto, Sunariyanto (Universitas Nahdlatul Ulama Blitar, 2024)
The progress of the current era has made digital development more advanced. All activities are easier to do in the digital world, especially in the shopping sector. Shopping can be done only with a smartphone, which can lead to consumer behavior in individuals. This research aims to identify the influence of digital culture on consumer behavior. This research method uses descriptive quantitative by distributing a Google Form questionnaire which then uses random sampling techniques. The results obtained in this research indicate that there is an influence between e-lifestyle on consumer behavior because lifestyle makes a person's behavior uncontrolled. This causes purchasing power not to match needs due to the large number of advertisements and the influence of the digital world. Furthermore, digital culture has no influence on consumer behavior because advances in the digital era can be used in various sectors such as work and education, not just social media and e-commerce. The results of research on the influence of e-lifestyle and digital culture on consumer behavior show that it has an influence but is not dominant because there are many factors that occur outside e-lifestyle and digital culture.Â